ANTIBIOTIC RESISTANCE OF ACTINOBACILLUS PLEUROPNEUMONIAE IN SWINE: PROBLEMS AND SOLUTIONS - V. S. Rusaleyev (Ветеринария сегодня)
Porcine pleuropneumonia is an infectious contagious disease caused by bacteria Actinobacillus pleuropneumoniae. Currently, the disease is widespread in many countries with well-developed pig production. The disease causes significant economic damage to farms due to the large mortality and expenses for treatment of diseased pigs and implementation of veterinary and sanitary measures. Due to increased number of Actinobacillus pleuropneumoniae cases in pigs, and the emergence of actinobacillus-resistant forms, it is necessary to perform a more thorough study and discussion of this problem. The disease epidemic surveillance is based on continuous monitoring aimed at porcine Actinobacillus pleuropneumoniae identification, confirmation and registration, determination of its characteristics and trends in development of sensitivity to antimicrobial preparations. The article addresses the topic of antibiotic use and the antibiotic resistance of microorganisms, which is actual not only for veterinary medicine but also for medicine. The model of swine Actinobacillus pleuropneumoniae was used to study the reasons of antibiotic resistance. Possible approaches to overcoming the resistance of actinobacilli to antibiotics have been discussed. The prospects for the use of antibiotics were discussed in detail to cope with this problem. Targeted surveillance, aimed at monitoring and collecting information on the prescription of antibiotics is of great importance for the solution of the problem of antibiotic resistance. The information obtained from the monitoring can be used for development of the plan and strategy for the use of antibacterial preparations (preparation selection, dose, route of administration, frequency, number of courses), development and implementation of more effective approaches to the treatment of Actinobacillus pleuropneumoniae in pigs, control of the antibiotic-resistant bacteria occurrence and spread.